CONTRIBUTION OF THE “SANGGAR JUARA” IN FORMING CHILDREN’S CHARACTER - Shera Amalia Ghaitsa; Wahyunengsih Wahyunengsih (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of carrying out this activity is as a form of Sanggar Juara’s concern for children's character education and to provide education in a more exciting way to children. In addition, the benefits of this activity for children apart from understanding character education, children can have more fun and play with their friends. The purpose of writing this article is to introduce the Sanggar Juara Organization to readers. The method used to achieve this goal is to use fun teaching methods by playing games, telling stories, and learning about practice directly. In conclusion, the champion school succeeded in carrying out community service activities for approximately five months and made the children at RPTRA Pinang Indah and RPTRA Mawar learn about character education.